2016
DOI: 10.1088/1475-7516/2016/04/006
|View full text |Cite
|
Sign up to set email alerts
|

Quantum corrections in Higgs inflation: the Standard Model case

Abstract: We compute the one-loop renormalization group equations for Standard Model Higgs inflation. The calculation is done in the Einstein frame, using a covariant formalism for the multi-field system. All counterterms, and thus the betafunctions, can be extracted from the radiative corrections to the two-point functions; the calculation of higher n-point functions then serves as a consistency check of the approach. We find that the theory is renormalizable in the effective field theory sense in the small, mid and la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
90
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 85 publications
1
90
0
Order By: Relevance
“…The above discussion applies only at classical level. Incorporating quantum corrections is a difficult task, although in the case of plateau potentials they have been shown to be mostly insignificant during inflation [26,65,97,98,[101][102][103][104][105][106][107][108][109]. However, they may affect the potential in the regime where reheating occurs [104,106], and certainly one should find a way to relate the couplings at the scale of inflation to the physics at lower energies, in particular around the EW scale.…”
Section: Higgs Inflationmentioning
confidence: 99%
“…The above discussion applies only at classical level. Incorporating quantum corrections is a difficult task, although in the case of plateau potentials they have been shown to be mostly insignificant during inflation [26,65,97,98,[101][102][103][104][105][106][107][108][109]. However, they may affect the potential in the regime where reheating occurs [104,106], and certainly one should find a way to relate the couplings at the scale of inflation to the physics at lower energies, in particular around the EW scale.…”
Section: Higgs Inflationmentioning
confidence: 99%
“…In the Einstein frame, the RG improved effective inflaton potential at the one-loop level is given by [47][48][49] …”
Section: Running B − L Higgs Inflation and Stability Of Inflaton Potementioning
confidence: 99%
“…Since RGE evolves logarithmically, to a good approximation we can analytically solve the RGE of λ around I such that β λ is taken to be constant. The solution is given by 5 In this RG improved effective potential, we have identified the renormalization scale with according to the prescription proposed in [47][48][49], where it has been shown that the effective potential is frameindependent with this choice. In fact, we are especially interested in the parameter region of ξ 1 in this paper, so that φ and the identification reduces to the usual one.…”
Section: Running B − L Higgs Inflation and Stability Of Inflaton Potementioning
confidence: 99%
See 1 more Smart Citation
“…If one reads off the beta function of the "quartic" coupling from the combination λ ch +λ km , it changes suddenly at h ∼ µ km ; see e.g. Refs [94,95]…”
mentioning
confidence: 99%